2011
DOI: 10.1001/archsurg.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Elective Liver Resections in a Center With Low Mortality

Abstract: To develop a score predicting the morbidity of liver resections in a center with low mortality. Design, Setting, and Patients: The study was based on a prospective database of all liver resections performed at the Geneva University Hospitals between January 1, 1991, and October 30, 2009 (a total of 726 elective liver resections in 689 patients). Perioperative complications and their severity were graded according to the original classification by Clavien et al. Variables independently associated with the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 40 publications
3
58
1
2
Order By: Relevance
“…Although, all the liver resections were performed when the CTP class was A, 52% of death was caused by liver failure (12/23), probably owing to the damaged hepatic parenchyma of HBV and better function of other organs. With an overall 30.1% morbidity rate, our results were consistent with those reported in recent studies [1], [3], [6], [7], [8], [9], [10]. Death was rare in our cohort, therefore it was not analyzed alone and combined with other lethal complication(complication III–IV).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although, all the liver resections were performed when the CTP class was A, 52% of death was caused by liver failure (12/23), probably owing to the damaged hepatic parenchyma of HBV and better function of other organs. With an overall 30.1% morbidity rate, our results were consistent with those reported in recent studies [1], [3], [6], [7], [8], [9], [10]. Death was rare in our cohort, therefore it was not analyzed alone and combined with other lethal complication(complication III–IV).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the focus of liver surgery has turned on strategies to prevent nonlethal complications and develop tools to identify preoperatively potential patients at higher risk for severe complications [1]. Many factors may contribute to postoperative complications and have been verified by other studies [1], [2], [6][14], including liver function, portal hypertension, extent of liver resection,blood loss and anesthesiologists category and so on. To prevent complications,it is essential to identify, ideally preoperatively, those patients at risk to develop poor outcome and perform prevention strategies [14].…”
Section: Introductionmentioning
confidence: 99%
“…Major liver resection is a known risk factor for postoperative complications [12,13,[28][29][30][31][32][33][34][35] . In this study, it was identified in multivariate analysis as an independent risk factor for RSR-significant morbidity and RSR reinterventions.…”
Section: Discussionmentioning
confidence: 99%
“…With minimally invasive surgery, surgical stress is reduced, whether it is by a robotic or a laparoscopic approach. Besides, as for laparoscopy [25,32], the robotic results compare more than favorably with open surgery [33], notably by minimizing blood loss and the risk of transfusion (in the selected published patients).…”
Section: Expert Commentarymentioning
confidence: 99%